Conditioned Flavor Preference and the US Postexposure Effect in the House Musk Shrew (Suncus Murinus) - Sawa, Kosuke; Ishii, Kiyoshi (Frontiers in Psychology, 2012)
The house musk shrew (Suncus murinus) is the only species of insectivore that can be used as a laboratory animal and is an interesting subject in terms of evolutional and comparative aspects. The present study on the learning faculties of shrews examines the possibility of acquiring a conditioned flavor preference and the effects of US postexposure. Subjects were allowed to a drink sucrose solution with flavor A and tap water with flavor B during training. Two extinction tests were administered after every four conditioning trials, and a significant preference for flavor A was observed. After each test, the animals were divided into two groups. Subjects in Group US were presented with a sucrose solution without flavor, while those in Group Water were given tap water. After these trials, all subjects received choice tests where they were presented with water containing the two flavors. The preference ratio was lower in Group US than in Group Water, suggesting a postexposure effect. The findings were discussed in terms of habituation to the US.